Revolutionizing logistics: the road to electrifying goods transport vehicles in India (2025)
The electrification of goods transport vehicles has emerged as a crucial solution for the environmental and economic issues associated with traditional transportation systems. Progress in battery technology has significantly improved the feasibility of electrifying goods transport vehicles. Nonetheless, there are notable challenges that need to be addressed, including limited charging infrastructure, limited range, and high upfront costs, which serve as significant barriers to widespread electrification adoption in India. This paper provides a comprehensive overview of the status of electrification in goods transport vehicles, emphasizing the environmental benefits, technological advancements, existing challenges, and possible solutions in the Indian Heavy Commercial Vehicle (HCV) segment.